INTERPRETATION OF THE MOTHER ARCHETYPE IN UZBEK AND ENGLISH NOVELS: BASED ON THE WORKS OF TOGAY MUROD AND D.H LAWRENCE (Qo‘qon DPI. Ilmiy xabarlar jurnali, 2026)
The archetype is a system of universal images that has existed since antiquity in human culture and literature. Recurring across the creative work of different peoples, it allows a literary work to reveal its national and universal layers at the same time. Within literary studies, archetypal analysis is recognized as an important scholarly tool, particularly in comparative research. This article examines the literary interpretation of the mother archetype in Togay Murod’s novel “Otamdan qolgan dalalar” (“Fields Left by My Father”) and D.H. Lawrence’s “Sons and Lovers” through a comparative-analytical approach. The study draws on C.G. Jung’s theory of archetypes, psychoanalytic literary criticism, and comparative close reading. The findings show that in “Otamdan qolgan dalalar” the mother archetype appears predominantly as the positive Great Mother within a national and cultural context, whereas in “Sons and Lovers” the figure of Gertrude Morel embodies the archetype’s dual nature, at once nurturing and possessive. Although the mother archetype is universal, its literary interpretation differs fundamentally according to the national and cultural environment, and this difference reveals the distinctive artistic and spiritual world of each people.